Family tourism development in the new era of tourism: Korean tourists’ domestic trip preferences for accommodation, travel duration, destination, and natural environment - Soyeun (Olivia) Lee; JooHyang Kim; Heesup Han (Humanities & Social Sciences Communications, 2023)
Abstract This study identifies the main selection attributes of potential Korean domestic family tourists using a choice experiment (CE) and then figures out how much money they are willing to pay for each attribute. This paper uncovered that there are differences in preference patterns across income level and the presence of children. The family travelers preferred shorter travel times, two nights and 3 days for travel duration, resort/condominium, low media/SNS exposure places, and natural scenery or relaxing. In addition, a strong preference for natural scenery or relaxing induces the highest marginal-willingness-to-pay (MWTP) regardless of the income level and the presence of children. This study has academic significance as it presents the appropriate value estimation for each attribute through MWTP assessment, offering essential foundational data for establishing reasonable pricing for tourism products.